Produção IN VITRO de Embriões Bovinos. - Souza, Isadora Afonsa de (Universidade Federal do Tocantins, 2023)
The in vitro production of embryos has been highlighting the world livestock market by enabling the selection and multiplication of genetically superior animals and increasing the number of births per female. Brazil has established itself as the country with the largest application of breeding biotechnologies in bovines in the world, being considered the largest in vitro embryo producer responsible for 85% of production. This highlight is due to the fact that the country is the main exporter of beef and has the largest commercial herd in the world, where the North has the second largest Brazilian herd. Currently many researches are being carried out with the aim of maximizing in vitro production by improving the production rate and quality of embryos, for which many protocols with different culture media and times are widely explored. In addition other factors are indicated as influencers in the results such as: the effects related to the bull, the effects related to the donor and the effects of the transport of these oocytes. Due to this, this work has as objective to make an approach on the in vitro production of embryos describing its aspects, techniques and the factors that imply in obtaining good results, in addition, to expose the development of the technique in the state of Pará.